Criminal Violations of the Medical Ethics Code by Dr. Bimanesh - Naomi Jesica Hartanto; Arlene Agustina; Klarika Permana (Fiat Justisia: Jurnal Ilmu Hukum, 2018)
The relationship between doctors and patients is no longer seen as a mere relationship of trust, the relationship has been seen as a contractual relationship. The relationship between doctor and patient is an agreement known as a therapeutic transaction. Doctors as members of professions that devote their knowledge to the public interest have freedom and independence-oriented to human values in accordance with the medical code of ethics. The medical code of ethics is regulated in the Indonesian Medical Ethics Code (KODEKI). The doctor's profession is required to work professionally and uphold the Code of Medical Ethics in carrying out his profession. However, there are some doctors who do not do their profession professionally. One of them, the case of Doctor Bimanesh Sutarjo allegedly cooperating to falsify Setya Novato's suspect to the hospital to be hospitalized with medical data that was allegedly manipulated in such a way as to avoid calls and checks by KPK investigators. Therefore, the authors are interested in writing this journal so that we understand better about the violations and law enforcement against KODEKI violations.Keywords: Indonesian Medical Ethics Code (KODEKI), doctors, Doctor Bimanesh